(untitled) (Orthopaedic SPOT, 2025)
Introduction: The article presents a descriptive analysis of tennis injuries among athletes participating in the Porto Open, an outside, hard court tournament encompassed within the ATP 125 category in the tennis circuit. This study aims to provide insights into injury patterns, its prevalence, and potential risk factors. Methods: We conducted a retrospective observational study to analyze tennis‐related injuries among athletes participating in the Porto Open 2023. Results:The study included 50 male athletes from 20 different nationalities, with Portuguese (n=13; 26%) and French (n=12; 24%) nationalities being the most frequent. Conclusion: Through an examination of the different types of injuries, affected anatomical regions, and injury mechanisms, this analysis aims to provide pertinent insights to enhance injury prevention strategies and promote the overall well‐being of athletes.